A Linearly Polarized Ho:YAG Laser at 2.09 μm with Corner Cube Cavity Pumped by Tm:YLF Laser*Supported by the National Natural Science Foundation of China under Grant Nos 61308009 and 61405047, the China Postdoctoral Science Foundation Funded Project under Grant No 2013M540288, the Fundamental Research Funds for the Central Universities under Grant Nos HIT.NSRIF.2014044 and HIT.NSRIF.2015042, and the Science Fund for Outstanding Youths of Heilongjiang Province under Grant No JQ201310. (July 2015) - Wu, Jing; Ju, You-Lun; Dai, Tong-Yu; Liu, Wei; Yao, Bao-Quan; Wang, Yue-Zhu
<x content-type="archive" xml:space="preserve">Abstract</x> A linearly polarized operation Ho:YAG laser at 2090.5nm with a corner cube cavity is demonstrated. A polarizer with high reflectivity for the s-polarized light at the laser wavelength is employed to achieve a linearly polarized laser. In the same case of resonator length, the corner cube can be used to cut the volume of the Ho:YAG laser and to enhance the stability of the system. The maximum linearly polarized output power of 5.8 W is achieved at the absorbed pump power of 23.3 W, corresponding to a slope efficiency of 29.7%, and the optical-optical conversion efficiency is around 24.9%. The M2 factors of the 2.09 μm laser are 2.4 and 1.2 along the horizontal and vertical directions, respectively.